Li-based composite anode for solid state battery and manufacturing method thereof
By using lithium-based composite anode in the anode of the sulfide all-solid state battery pack, the short circuit risk and capacity loss problems caused by lithium dendrites are solved, and higher battery stability and capacity maintenance are achieved.
Patent Information
- Application Number
- CN202311050321.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
In sulfide all-solid state battery packs, the non-uniform deposition of lithium at the anode leads to the formation of lithium dendrites, increasing the risk of short circuit and the possibility of battery capacity loss.
A lithium-based composite anode is designed, including a lithium metal layer and a metal sulfide layer or particles. The metal sulfide can be used as a continuous layer, embedded on the surface of the lithium metal layer or dispersed in the volume of the lithium metal layer to reduce the formation of dendrites. .
By using lithium-based composite anode, the formation of lithium dendrites is reduced, the risk of short circuit is reduced and the capacity retention capability of the battery is improved.
Smart Images

Figure CN119495794A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solid-state batteries and methods of making the same, and in particular to lithium-based composite anodes for dendrite-free all-solid-state batteries. Background Art
[0002] All-solid-state batteries (ASSBs) using sulfide electrolytes have the potential to outperform prior art lithium-ion batteries (LIBs) in terms of abuse tolerance and operating temperature range. For example, when thin lithium metal foil is used as an anode in an ASSB, high energy density can be achieved due to the relatively high density of the solid electrolyte (SSE) compared to liquid electrolytes. Unfortunately, lithium dendrites are often formed during battery operation due to the non-uniform deposition of lithium at the anode. These dendrites cause short circuit risks and capacity loss of the battery. Specifically, for sulfide-based all-solid-state batteries (S-ASSBs), if a pressure greater than 50 psi is not applied during operation to strengthen the grain boundaries between the SSE particles, the battery forms lithium dendrites, which lead to internal short circuits, especially when the capacity loading is relatively high.
[0003] Figure 1A and 1B A lithium metal anode 12 in contact with a sulfide solid electrolyte 10 is depicted before and after electrical cycling. The lithium metal reacts with the sulfide solid electrolyte, and the interface resistance increases due to the appearance of the interface side reaction product 14. The sulfide solid electrolyte 10 is Li 6 PS 5 Cl. Figure 1A is a micrograph showing that no dendrites were formed before cycling, whereas Figure 1B is a micrograph showing the formation of lithium dendrites at grain boundaries after some cycles have occurred 16. Cracks also appeared in the solid electrolyte 18, which increased the cell resistance. The cathode mixture with a high mass loading - which contained cathode active material, lithium sulfide electrolyte and conductive carbon (at 30 mg / cm 2 The battery cannot be fully charged even during the initial cycle at relatively low temperatures (e.g., 25°C).
[0004] It would therefore be desirable to provide a lithium-based composite anode designed to inhibit dendrite formation. Summary of the invention
[0005] This application involves the following:
[0006] [1] A solid-state battery cell comprising:
[0007] anode;
[0008] cathode; and
[0009] A solid electrolyte is disposed between an anode and a cathode; wherein the anode is a lithium metal composite anode comprising a lithium metal layer and a metal sulfide.
[0010] [2] The battery cell as described in [1] above, wherein the metal sulfide is provided as a continuous layer on the lithium metal layer.
[0011] [3] The battery cell as described in [1] above, wherein the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer.
[0012] [4] The battery cell as described in [1] above, wherein the metal sulfide is in the form of particles dispersed in the volume of the lithium metal layer.
[0013] [5] The battery cell as described in [1] above, wherein the metal sulfide is indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide or a combination thereof.
[0014] [6] The battery cell as described in [2] above, wherein the thickness ratio of the metal sulfide continuous layer to the lithium metal layer varies from 0.01:1 to 0.5:1.
[0015] [7] The battery cell as described in [2] above, wherein the metal sulfide continuous layer has a thickness of 0.001 μm to 50 μm.
[0016] [8] The battery cell as described in [3] above, wherein the particles are disposed on the lithium metal layer in an amount effective to cover 10 to 90% of the total surface area of the lithium metal layer.
[0017] [9] The battery cell as described in [4] above, wherein the particles dispersed in the volume of the lithium metal layer occupy 1 to 50% of the total volume of the lithium metal composite anode.
[0018]
[10] The battery cell as described in [1] above, wherein the cathode comprises a cathode current collector electrically connected to a cathode active layer; wherein the cathode active layer comprises a cathode active material, a conductive additive, a solid electrolyte and a polymer binder.
[0019]
[11] . The battery cell as described in
[10] above, wherein the cathode active material is lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate oxide, lithium nickel cobalt aluminum oxide, spinel or a combination thereof.
[0020]
[12] The battery cell as described in
[10] above, wherein the lithium nickel manganese cobalt oxide is LiNi x Mn y Co (1-x-y) O 2; The lithium nickel cobalt aluminum oxide is LiNi x Mn y Al (1-x-y) O 2 , the lithium nickel manganese oxide is LiNi x Mn (1-x) O 2 , wherein in each case x is from 0.7 to 0.85 and y is less than 0.15.
[0021]
[13] A battery cell as described in [1] above, wherein the solid electrolyte comprises Li 2 SP 2 S 5 System, Li 2 S-SnS 2 System, Li 2 S-SiS 2 System, Li 2 S-GeS 2 System, Li 2 SB 2 S 3 System, Li 2 S-Ga 2 S 3 System, Li 2 SP 2 S 3 System, Li 2 S-Al 2 S 3 System, Li 2 O-Li 2 SP 2 S 5 System, Li 2 SP 2 S 5 -P 2 O 5 System, Li 2 SP 2 S 5 -GeS 2 System, Li 2 SP 2 S 5 -LiX system, where X = F, Cl, Br or I; Li 2 S-As 2 S 5 -SnS 2 System, Li 2 SP 2 S 5 -Al 2 S 3 System, Li 2S-LiX-SiS 2 , wherein X=F, Cl, Br or I.
[0022]
[14] A method of manufacturing a battery cell, comprising:
[0023] A lithium metal composite anode is arranged on the anode current collector; wherein the lithium metal composite anode comprises a lithium metal layer and a metal sulfide;
[0024] Disposing a solid electrolyte on the lithium metal composite anode;
[0025] disposing a cathode active layer on the solid electrolyte; and
[0026] A cathode current collector is disposed on the cathode active layer.
[0027]
[15] The method as described in
[14] above, wherein the metal sulfide is arranged as a continuous layer on the lithium metal layer.
[0028]
[16] The method as described in
[14] above, wherein the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer.
[0029]
[17] The method as described in
[14] above, wherein the metal sulfide is in the form of particles dispersed in the volume of the lithium metal layer.
[0030]
[18] . The method as described in
[14] above, wherein the metal sulfide is indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide or a combination thereof.
[0031]
[19] The method as described in
[15] above, wherein the thickness ratio of the metal sulfide continuous layer to the lithium metal layer varies from 0.01:1 to 0.5:1.
[0032]
[20] . The method as described in
[19] above, wherein the metal sulfide continuous layer has a thickness of 0.001 μm to 50 μm.
[0033] In an exemplary embodiment, a solid-state battery cell includes an anode, a cathode, and a solid electrolyte disposed between the anode and the cathode. The anode is a lithium metal composite anode comprising a lithium metal layer and a metal sulfide.
[0034] In addition to one or more features described herein, the metal sulfide is disposed as a continuous layer on the lithium metal layer.
[0035] In yet another exemplary embodiment, the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer.
[0036] In yet another exemplary embodiment, the metal sulfide is in the form of particles dispersed within the volume of the lithium metal layer.
[0037] In yet another exemplary embodiment, the metal sulfide is indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide, or a combination thereof.
[0038] In yet another exemplary embodiment, the thickness ratio of the continuous metal sulfide layer to the lithium metal layer varies from 0.01:1 to 0.5:1.
[0039] In yet another exemplary embodiment, the continuous metal sulfide layer has a thickness of 0.001 micrometers to 50 micrometers.
[0040] In yet another exemplary embodiment, the metal sulfide particles are disposed on the lithium metal layer in an amount effective to cover an area of 10 to 90% of the total surface area of the lithium metal layer.
[0041] In yet another exemplary embodiment, the metal sulfide particles dispersed in the lithium metal layer occupy 1 to 50% of the total volume of the lithium metal composite anode.
[0042] In yet another exemplary embodiment, the cathode includes a cathode current collector in electrical communication with a cathode active layer; wherein the cathode active layer comprises a cathode active material, a conductive additive, a solid electrolyte, and a polymer binder.
[0043] In yet another exemplary embodiment, the cathode active material is lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate oxide, lithium nickel cobalt aluminum oxide, spinel, or a combination thereof.
[0044] In yet another exemplary embodiment, the lithium nickel manganese cobalt oxide is LiNi x Mn y Co (1-x-y) O 2 ; The lithium nickel cobalt aluminum oxide is LiNi x Mn y Al (1-x-y) O 2 , the lithium nickel manganese oxide is LiNi x Mn (1-x) O 2 , wherein in each case x is from 0.7 to 0.85 and y is less than 0.15.
[0045] In yet another exemplary embodiment, the solid electrolyte includes Li 2 SP 2 S 5 System, Li 2 S-SnS2 System, Li 2 S-SiS 2 System, Li 2 S-GeS 2 System, Li 2 SB 2 S 3 System, Li 2 S-Ga 2 S 3 System, Li 2 SP 2 S 3 System, Li 2 S-Al 2 S 3 System, Li 2 O-Li 2 SP 2 S 5 System, Li 2 SP 2 S 5 -P 2 O 5 System, Li 2 SP 2 S 5 -GeS 2 System, Li 2 SP 2 S 5 -LiX system, where X = F, Cl, Br or I; Li 2 S-As 2 S 5 -SnS 2 System, Li 2 SP 2 S 5 -Al 2 S 3 System, Li 2 S-LiX-SiS 2 , wherein X=F, Cl, Br or I.
[0046] In an exemplary embodiment, a method of making a battery cell includes disposing a lithium metal composite anode on an anode current collector, wherein the lithium metal composite anode comprises a lithium metal layer and a metal sulfide. A solid electrolyte is then disposed on the lithium metal composite anode. A cathode active layer is disposed on the solid electrolyte, and a cathode current collector is disposed on the cathode active layer.
[0047] In addition to one or more features described herein, the metal sulfide is disposed as a continuous layer on the lithium metal layer.
[0048] In yet another exemplary embodiment, the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer.
[0049] In yet another exemplary embodiment, the metal sulfide is in the form of particles dispersed within the volume of the lithium metal layer.
[0050] In yet another exemplary embodiment, the metal sulfide is indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide, or a combination thereof.
[0051] In yet another exemplary embodiment, the thickness ratio of the continuous metal sulfide layer to the lithium metal layer varies from 0.01:1 to 0.5:1.
[0052] In yet another exemplary embodiment, the continuous metal sulfide layer has a thickness of 0.001 micrometers to 50 micrometers.
[0053] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings.
[0054] BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Additional features, advantages and details are shown, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0056] Figure 1A is a micrograph showing the absence of dendrite formation before cycling;
[0057] Figure 1B is a micrograph showing the formation of lithium dendrites at grain boundaries after some cycles have been performed;
[0058] Figure 2A depicts an exemplary multilayer lithium metal composite anode;
[0059] Figure 2B depicts a lithium metal composite anode in which metal sulfide particles are partially embedded in a lithium metal layer;
[0060] Figure 2C depicts a volume dispersed lithium metal composite anode in which metal sulfide particles are distributed throughout a lithium metal layer;
[0061] Figure 3 An exemplary method of disposing metal sulfide particles on a surface of a lithium metal layer is depicted; and
[0062] Figure 4 is a charge-discharge graph, which plots voltage vs 10 mg / cm 2 and 30mg / cm 2 capacity under load. DETAILED DESCRIPTION
[0063] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.
[0064] According to an exemplary embodiment, an anode composition is disclosed herein, comprising metallic lithium and a metal sulfide. In the anode composition, the metal sulfide may be disposed on the surface of the lithium metal in the form of a continuous layer, embedded on the surface of the lithium metal, or dispersed within the volume of the lithium metal. In one embodiment, the metal sulfide reacts with the lithium metal to produce lithium sulfide and an alloy of lithium and the metal. This results in reduced dendrite formation during battery operation. The reduction in dendrite formation minimizes short circuits and increases battery capacity.
[0065] Figure 2A , 2B 2C depict three exemplary embodiments of cross-sectional areas of solid-state battery cells using sulfide solid-state electrolytes. Figure 2A , 2B In all battery cells in the 2C, the same numbers are used to represent the same components. Figure 2A , 2B Each battery cell 100 in 2C and 2C comprises an anode current collector 102, a lithium metal composite anode 104, and the lithium metal composite anode 104 comprises a lithium metal layer 104A in contact with a metal sulfide 104B. The lithium anode 104 contacts a first surface of a solid electrolyte layer 106. The opposite second surface of the solid electrolyte layer 106 contacts a cathode active layer 108, which in turn contacts a cathode current collector 110. The anode of the battery cell 100 thus comprises an anode current collector 102 and a lithium metal composite anode 104. The cathode of the battery cell 100 thus comprises a cathode current collector 110 and a cathode active layer 108.
[0066] Figure 2A , 2B 2C depict different arrangements of the lithium metal composite anode 104. Figure 2A In the embodiment, the lithium metal composite anode is a multi-layer anode in which the metal sulfide layer 104B is disposed on the lithium metal layer 104A. Figure 2B In the embodiment, the metal sulfide is in the form of particles 104C (hereinafter referred to as metal sulfide particles 104C) dispersed on the surface of the lithium metal layer 104A. Figure 2B In the embodiment, the metal sulfide particles 104C may be partially embedded in the surface of the lithium metal layer 104A. Figure 2C In the embodiment, the metal sulfide particles 104C are completely embedded in the volume of the lithium metal layer 104A. It should be noted that the Figure 2A ,2B and combinations of those depicted in 2C, even though they may not be explicitly described in detail. For example, Figure 2B The configuration of 2C can be combined with the configuration of 2C (not shown here) so that the metal sulfide particles 104C can be dispersed on the surface of the lithium metal layer 104A and dispersed throughout the volume of the lithium metal layer 104A. Alternatively, Figure 2A The construction can be Figure 2C The structural combination makes the metal sulfide layer 104B disposed on the surface of the lithium metal layer 104A, while the metal sulfide particles 104C are disposed throughout the volume of the lithium metal layer 104A.
[0067] Now refer to Figure 2A The anode current collector 102 is generally a metal film or metal mesh including copper, nickel, stainless steel or a combination thereof. The anode current collector 102 has a lithium metal composite anode 104 disposed thereon, the lithium metal composite anode 104 including a lithium metal layer 104A and a metal sulfide layer 104B. Figure 2A , the lithium metal layer 104A contains only lithium metal with a thickness of 0.1 to 100 microns. The lithium metal layer 104A directly contacts the anode current collector 102. Disposed on the lithium metal layer 104A is a metal sulfide layer 104B. The lithium metal layer 104A contacts the metal sulfide layer 104B at a single interface 105.
[0068] The thickness of the metal sulfide layer 104B is less than the thickness of the lithium metal layer 104A. In one embodiment, the thickness ratio of the metal sulfide layer 104B to the lithium metal layer 104A varies from 0.01:1 to 0.5:1. The metal sulfide layer 104B has a thickness of 0.001 micrometers to 50 micrometers.
[0069] Now refer to Figure 2B, it can be seen that the metal sulfide particles 104C are partially embedded in the lithium metal layer 104A. In other words, the lithium metal layer 104A has a surface changed by the presence of the metal sulfide particles 104C. In this embodiment, a plurality of metal sulfide particles 104C protrude from the surface of the lithium metal layer 104A. The remaining portion of the metal sulfide particles 104C protrudes into the surface of the lithium metal layer 104A. Some metal sulfide particles 104C may be disposed on the surface of the lithium metal layer 104A without actually being embedded in the metal layer 104A. The metal sulfide particles 104C have an average particle size of 50 to 20,000 nanometers. The particle size herein refers to the cross-sectional diameter of the particles measured using a scanning electron microscope. In order to determine the average particle size, a plurality of particles are imaged using a scanning electron microscope, and the average diameter is then calculated by adding all diameters and dividing the sum by the total number of particles. The metal sulfide particles 104C are disposed on the lithium metal layer 104A in an amount effective to cover an area of 10% to 90% of the total surface area of the lithium metal layer 104A. In one embodiment, the thickness of the lithium metal layer 104A (containing the metal sulfide particles 104C) can be increased because the thickness must accommodate the volume of the lithium metal as well as the volume of the metal sulfide particles 104C.
[0070] Figure 2C An alternative embodiment is depicted in which the lithium metal layer 104A has metal sulfide particles 104C already embedded within its volume. In this embodiment, the metal sulfide particles 104C are completely embedded in the lithium metal layer 104A and preferably do not protrude from its surface. The metal sulfide particles 104C embedded in the lithium metal layer 104A occupy 1 to 50%, preferably 5 to 35%, of the total volume of the lithium metal composite anode 104.
[0071] The metal sulfide used in the metal sulfide layer 104B or the metal sulfide particles 104C includes indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide, or a combination thereof.
[0072] The metal sulfide layer 104B or metal sulfide particles 104C may be combined with the lithium metal layer 104A in several different ways to form the lithium metal composite anode 104. These will be briefly described in detail below.
[0073] In one embodiment, the metal sulfide layer 104B may be disposed on the lithium metal layer 104A via physical vapor deposition. The lithium metal layer 104A is first disposed on the anode current collector 102, and then a metal sulfide layer 104B of a desired thickness may be sputtered on the lithium metal layer 104A using a magnetron to form the lithium metal composite anode 104. In another embodiment, the lithium metal layer 104A may be evaporated onto the metal sulfide layer 104B. In this embodiment, a metal sulfide film of a desired thickness is used as a substrate, on which the lithium metal layer 104A is evaporated to form the lithium metal composite anode 104.
[0074] In another embodiment, a slurry of metal sulfide is prepared using a solvent and an optional binder. The slurry is then disposed (coated or applied) on the lithium metal layer 104A and dried to form the metal sulfide layer 104B. The result is a metal sulfide layer 104B disposed on the lithium metal layer 104A, forming the lithium metal composite anode 104.
[0075] Figure 3 An exemplary embodiment of manufacturing a lithium metal composite anode 104 is depicted in which metal sulfide particles 104C are partially embedded in the surface of the lithium metal layer 104A. This embodiment is depicted in the above Figure 2B A spray system 202C filled with metal sulfide particles 104C (or a suspension of metal sulfide particles) discharges the particles onto the lithium metal sheet 104A. A pair of rollers 202A and 202B apply a combination of shear and compression forces on the metal sulfide particles 104C, thereby causing them to be partially embedded in the lithium metal layer 104A and forming a lithium metal composite anode 104.
[0076] In another embodiment, the metal sulfide particles 104C can be completely embedded in the lithium metal layer 104A (to produce Figure 2C Lithium metal composite anode 104): Metal sulfide particles 104C are first mixed with lithium metal particles to form a particle mixture. The particle mixture is heated to a temperature above the melting point of lithium (357°F) and then cast. Since the metal sulfide particles melt at a higher temperature than lithium metal (indium sulfide melts at 1922°F), they do not undergo any state change. The melt in which the metal sulfide particles are dispersed is then cast on a substrate (or in a mold) and cooled to form a lithium metal composite anode 104 (depicted in FIG. 1 ). Figure 2C Even if the metal sulfide particles melt at a lower temperature than the lithium metal, as long as the metal sulfide molten particles remain dispersed in the molten lithium metal, Figure 2C The structure depicted in .
[0077] The following description details the fabrication and testing of a solid-state battery pack having Figure 2A , 2B and the lithium metal composite anode 104 depicted in 2C. Now referring again to Figure 2A , 2B 2C, after the lithium metal composite anode 104 is manufactured as described in detail above, the lithium metal composite anode 104 is disposed on the anode current collector 102. On the surface 222 opposite to the surface 212 contacting the anode current collector 102, the solid electrolyte layer 106 is disposed on the lithium metal composite anode 104.
[0078] The solid electrolyte layer 106 comprises a solid electrolyte combined with a polymer binder. The solid electrolyte generally comprises a pseudo binary sulfide, a pseudo ternary sulfide, a pseudo quaternary sulfide, or a combination thereof. Examples of pseudo binary sulfides include Li 2 SP 2 S 5 System (such as Li 3 PS 4 , Li 7 P 3 S 11 and Li 9.6 P 3 S 12 )、Li 2 S-SnS 2 System (such as Li 4 S N 4 )、Li 2 S-SiS 2 System, Li 2 S-GeS 2 System, Li 2 SB 2 S 3 System, Li 2 S-Ga 2 S 3 System, Li 2 SP 2 S 3 System, Li 2 S-Al 2 S 3 Examples of pseudo-ternary sulfides include Li 2 O-Li 2 SP 2 S 5 System, Li 2 SP 2 S 5 -P 2 O 5 System, Li 2 SP 2 S 5 -GeS 2System (such as Li 3.25 Ge 0.25 P 0.75 S 4 and Li 10 G 2 S 12 )、Li 2 SP 2 S 5 -LiX system (wherein X = F, Cl, Br or I, examples of which include Li 6 PS 5 Br, Li 6 PS 5 Cl, L 7 P 2 S 8 I and Li 4 PS 4 I) Li 2 S-As 2 S 5 -SnS 2 System (such as Li 3.833 Sn 0.833 As 0.166 S 4 )、Li 2 SP 2 S 5 -Al 2 S 3 System, Li 2 S-LiX-SiS 2 (where X = F, Cl, Br or I, examples of which include 0.4LiI·0.6Li 4 S N 4 and Li 11 Si 2 PS 12 ).
[0079] The preferred solid electrolyte is Li 6 PS 5 The solid electrolyte is present in the solid electrolyte layer 106 in an amount greater than 80 wt%, preferably greater than 90 wt%, preferably greater than 98 wt%, and more preferably 100 wt%, based on the total weight of the electrolyte layer 106. The electrolyte layer 106 may optionally contain a binder that promotes the solid electrolyte particles to be bonded together so that they are not dispersed in the solid-state battery and that maintains the shape of the solid electrolyte layer 106.
[0080] The polymer binder generally comprises an organic polymer. The example of an organic polymer includes poly(tetrafluoroethylene) (PTFE), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), nitrile rubber (NBR), styrene-butadiene rubber (SBR), poly(propylene carbonate) (PPC), sodium carboxymethylcellulose (CMC), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-to-hexafluoropropylene) (PVDF-HFP), polyacrylonitrile (PAN), poly(vinylidene fluoride-to-chlorotrifluoroethylene) (P(VDF-CTFE)), poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TeFE)), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer (P(VDF-TrFE-CFE)) or a combination thereof. In a preferred embodiment, the polymer binder for the active layer is a poly(vinylidene fluoride-hexafluoropropylene) copolymer. The polymer binder has a weight average molecular weight of 5,000 to 1,000,000 g / mole, preferably 50,000 to 750,000 g / mole, and more preferably 75,000 to 500,000 g / mole as measured using gel permeation chromatography with polystyrene standards.
[0081] The polymer binder is optional, and if used is present in the solid electrolyte layer 106 in an amount less than 20 wt%, preferably less than 10 wt%, and more preferably less than 1 wt%.
[0082] Disposed on the surface 222 of the solid electrolyte layer 106 opposite the surface 212 contacting the lithium metal composite anode 104 is the cathode active layer 108, which in turn contacts the cathode current collector 110. The cathode active layer 108 comprises cathode active material, conductive additives, polymer binder and optionally a solid electrolyte.
[0083] The cathode active material may include lithium cobalt oxide (LCO, sometimes called "lithium cobaltate" or "spodumene" - one of its variants is LiCoO 2 ); lithium nickel manganese cobalt oxide (NMC, with a variant of LiNiMnCo); lithium manganese oxide (LMO, with a variant of LiMn 2 O 4 , Li 2 MnO 3 etc.); lithium nickel cobalt aluminum oxide (LiNiCoAlO 2 and its variants such as NCA) and lithium titanate oxide (LTO, a variant of Li 4 Ti 5 O 12 ); lithium iron phosphate (LFP, a variant of which is LiFePO 4), lithium nickel cobalt aluminum oxide (and its variants such as NCA) and other similar materials, spinel (LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 ), polyanion cathode (LiV 2 (PO 4 ) 3 ) and other lithium transition metal oxides. The surface-coated and / or doped cathode materials mentioned above, such as LiNbO 3 Coated LiMn 2 O 4 and Al-doped LiMn 2 O 4 Low voltage cathode materials such as lithiated metal oxides / sulfides (e.g. LiTiS 2 ), lithium sulfide and sulfur).
[0084] Other variations of the foregoing may be included. In some embodiments where NMC is used as the active material, a nickel-rich NMC may be used. For example, in some embodiments, a variation of the NMC may be LiNi x Mn y Co (1-x-y) O 2 、LiNi x Mn y Al (1-x-y) O 2 、LiNi x Mn (1-x) O 2 , Li 1+x MO 2 , wherein x is equal to or greater than about 0.7, 0.75, 0.80, 0.85 or greater, and wherein y is less than 0.15, preferably less than 0.1. In some embodiments, NMC811 may be used, wherein in the preceding formula, x is about 0.8 and y is about 0.1.
[0085] The cathode active materials may be used in the cathode active layer 108 in an amount of 50 to 98 wt %, preferably 70 to 95 wt %, based on the total weight of the cathode active layer.
[0086] The solid electrolytes that can be used for the cathode active layer 108 are listed above (in the section related to the solid electrolyte layer 106), and will not be listed again for the sake of brevity. The solid electrolyte can be used for the cathode active layer in an amount of up to 50 wt%, preferably less than 30 wt%, and more preferably less than 15 wt%, based on the total weight of the cathode active layer 108. In one embodiment, the solid electrolyte can be used for the cathode active layer in an amount of 1 wt% or more, preferably 2 wt% or more, based on the total weight of the cathode active layer 108.
[0087] The cathode active layer 108 also contains a conductive additive. The conductive additive preferably comprises a conductive carbonaceous material. Examples of conductive carbonaceous materials include carbon nanotubes, carbon black, activated carbon, graphene, graphite, graphite oxide, carbon fibers, etc., or a combination thereof. It is desirable that the conductive composition forms a conductive network extending from the surface of the cathode current collector 110 to the surface of the solid electrolyte layer 106.
[0088] Carbon nanotubes include single-walled carbon nanotubes (SWNT), double-walled carbon nanotubes (DWNT), multi-walled carbon nanotubes (MWNT) or combinations thereof and have a diameter of 2 to 100 nanometers, preferably 10 to 50 nanometers. They have a length of 20 to 10,000 nanometers, preferably 200 to 5000 nanometers. An aspect ratio greater than 10, preferably greater than 50 and more preferably greater than 100 is desirable.
[0089] Carbon black with a high surface area is preferred for electrodes. Carbon black (subclasses are acetylene black, channel black, furnace black, lamp black, and thermal black) is a material produced by the incomplete combustion of coal and coal tar, vegetable matter, or petroleum products (including fuel oil, fluid catalytic cracking tar, and ethylene cracked in limited supply of air). Carbon black is a form of quasi-crystalline carbon with a high surface area to volume ratio, although less than that of activated carbon. The surface area is 50 to 1000 m 2 / gm of carbon black may be used in the slurry used to form the electrode.
[0090] Activated carbon, also known as activated charcoal, is a carbon with a surface area of more than 3,000 m 2 / gm of carbon form. It can be used in combination with other conductive carbonaceous elements listed herein. An example of carbon black or activated carbon that can be used in the electrode forming slurry is KELTJEN TM Black or Super P.
[0091] Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a hexagonal lattice nanostructure. The graphene added to the slurry can be in the form of individual graphene sheets or in the form of multiple loosely connected graphene sheets. Each atom in the graphene sheet is connected to its three nearest neighbors by σ bonds and delocalized π bonds, which contribute to a valence band that extends across the entire sheet. This is the same type of bonding seen in carbon nanotubes and polycyclic aromatic hydrocarbons, as well as in fullerenes and glassy carbon. The valence band is in contact with the conduction band, making graphene a semimetal with unusual electronic properties that are best described by theories for massless relativistic particles.
[0092] Graphite particles can also be used in conductive compositions. Graphite is a natural manifestation of pure carbon with a hexagonal crystal structure, which is arranged in several parallel layers, called graphene layers. In short, a graphite particle contains multiple graphene sheets arranged parallel to each other. This anisotropic structure gives graphite special properties, such as conductivity along the individual layers or specific strength. It is extremely heat-resistant, with a sublimation point of over 3,800°C, highly thermally conductive and chemically inert.
[0093] Graphite oxide (GO), sometimes called graphene oxide, graphite oxide or graphitic acid, is a compound of carbon, oxygen and hydrogen in variable ratios, obtained by treating graphite with strong oxidants and acids to resolve additional metals. The largest oxidized bulk product is a yellow solid with a C:O ratio of 2.1:1 to 2.9:1, which retains the layer structure of graphite, but has much larger and irregular spacing. The bulk material disperses spontaneously in an alkaline solution, or can be dispersed by ultrasonic treatment in a polar solvent to produce a monomolecular sheet, analogous to graphene, which is called graphene oxide, i.e., graphite in a monolayer form. Graphene oxide sheets exist in the form of strong paper-like materials, films, thin films and composite materials, and can be used in electrode forming slurries for preparing the electrode.
[0094] Carbon fibers have a diameter of 5 to 10 microns and are primarily composed of carbon atoms. They may have a length greater than 1000 microns, preferably greater than 10,000 microns. The carbon fibers are prepared by drawing pitch or polyacrylonitrile polymer fibers under high pressure and at a temperature exceeding 1500° C., preferably at a temperature above 2200° C. Carbon fibers are different from carbon nanotubes and do not have concentrically arranged cylindrical graphene sheets. Carbon fibers typically contain high aspect ratio graphene sheets arranged in parallel to each other.
[0095] The aforementioned carbon nanotubes, carbon black, activated carbon, graphene sheets, graphite particles, graphite oxide particles or combinations thereof may be used alone or in any combination to form a conductive network. In an exemplary embodiment, carbon nanotubes are generally used in the largest amount when compared to other carbonaceous components.
[0096] The cathode active layer 108 may contain the conductive additive in an amount of up to 30 wt%, preferably less than 20 wt%, and more preferably less than 10 wt%, based on the total weight of the cathode active layer 108. In one embodiment, the cathode active layer 108 may contain the conductive additive in an amount of 1 wt% or more.
[0097] A polymer binder may also be used in the cathode active layer 108 to facilitate bonding of active material particles, conductive additives, and optional solid electrolytes. The polymer binder helps maintain the shape of the cathode active layer 108 and prevents the components of the cathode active layer 108 from dispersing throughout the battery pack. The polymer binders have been listed above and are not repeated here for the sake of brevity. The polymer binder is used in the cathode active layer 108 in an amount of up to 20 wt %, preferably less than 15 wt %, preferably less than 10 wt %, and more preferably less than 5 wt %, based on the total weight of the cathode active layer 108. In one embodiment, the cathode active layer 108 may contain the polymer binder in an amount of 1 wt % or more, preferably 2 wt % or more.
[0098] In one embodiment, in a method of making a solid-state battery, the anode current collector 102 (see Figure 2A ) having a lithium anode composite layer 104 (with Figure 2A , 2B and / or one of the forms depicted in 2C). The method for manufacturing the lithium anode composite layer 104 has been described in detail above and will not be described in detail again.
[0099] Subsequently, a solid electrolyte layer 106 and a cathode active layer 108 may be sequentially disposed on the lithium anode composite layer 104 in the form of slurry.
[0100] In order to prepare the slurry, the components of the solid electrolyte layer 106 or the components of the cathode active layer 108 are mixed with a suitable solvent. The solvent is preferably a solvent that does not interact with the solid electrolyte. After preparing each slurry (one for the solid electrolyte layer 106 and the other for the cathode active layer 108), the corresponding slurry is sequentially arranged on the lithium metal composite anode, and each slurry is dried before depositing the next slurry. When the solid electrolyte layer 106 and the cathode active layer 108 are both dried, the cathode current collector 110 is arranged on the cathode active layer 108 to form a solid-state battery 100. If necessary, the battery can be sealed in a housing (not shown).
[0101] The compositions and ingredients are detailed along with various methods of manufacture in the following non-limiting examples.
[0102] Example
[0103] Example 1
[0104] This example was conducted to determine the performance of a battery having a lithium metal composite anode compared to a battery whose anode contained only lithium metal. The lithium metal composite anode used herein is the one previously described in Figure 2A A multilayer anode of the type described in the literature, wherein a lithium metal layer has a metal sulfide layer (in this case indium sulfide In) disposed thereon. 2 S 3 ). The solid electrolyte layer contains Li 6 PS 5 Cl. No polymer binder was used to manufacture the anode. The material used in the anode was pressed in a compression mold at a pressure of 540 MPa to manufacture the anode.
[0105] The cathode active layer contains NCM 523 as the cathode active material. The solid electrolyte used for the cathode active layer is Li 6 PS 5 Cl. The conductive additive is Super P and the polymer binder is polytetrafluoroethylene. These are used as the cathode active layer in the following weight ratio: NCM523:L 6 PS 5 Cl∶SP∶PTFE=5∶4∶0.4∶0.094.
[0106] The comparative solid-state battery pack used only lithium metal as the anode. Except for the difference in the anode (the inventive battery pack having a lithium metal composite anode and the comparative battery pack having a lithium metal anode), the two battery packs were identical. Figure 4 The charge-discharge curves are shown, where the 2 and 30mg / cm 2 A graph of voltage (V) (300) vs capacity (mAh / g) (400) was plotted at a loading of 100 Å. Figure 4 The graph of shows the performance of three different battery packs, each with a different anode. Two of the battery packs have anodes containing only lithium metal (one with an anode containing a high loading of lithium metal (302) and the other with an anode containing only low levels of lithium metal (306)). One of the battery packs has a composite anode (304) containing a high level of lithium metal. From the results, it can be seen that the battery pack with the composite anode contributes to higher capacity, even at higher mass loadings, and without internal short circuits.
[0107] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. The term "or" means "and / or" unless the context clearly indicates otherwise. Reference to "aspects" throughout the specification means that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various aspects.
[0108] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0109] Unless specified to the contrary herein, all test standards are the most recent standards in effect as of the filing date of the present application or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0110] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0111] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope thereof. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the substantive scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. A solid-state battery cell comprising: anode; cathode; and A solid electrolyte is disposed between an anode and a cathode; wherein the anode is a lithium metal composite anode comprising a lithium metal layer and a metal sulfide.
2. The battery cell of claim 1, wherein the metal sulfide is disposed as a continuous layer on the lithium metal layer.
3. The battery cell of claim 1, wherein the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer.
4. The battery cell of claim 1, wherein the metal sulfide is in the form of particles dispersed within the volume of the lithium metal layer.
5. The battery cell of claim 1, wherein the metal sulfide is indium sulfide, aluminum sulfide, germanium sulfide, silicon sulfide, selenium sulfide, or a combination thereof.
6. The battery cell of claim 2, wherein the thickness ratio of the continuous layer of metal sulfide to the lithium metal layer varies from 0.01:1 to 0.5:
1.
7. The battery cell of claim 3, wherein the particles are disposed on the lithium metal layer in an amount effective to cover an area of 10 to 90% of the total surface area of the lithium metal layer.
8. The battery cell of claim 4, wherein the particles dispersed within the volume of the lithium metal layer occupy from 1 to 50% of the total volume of the lithium metal composite anode.
9. A method of manufacturing a battery cell, comprising: Disposing a lithium metal composite anode on the anode current collector; wherein the lithium metal composite anode comprises a lithium metal layer and a metal sulfide; Disposing a solid electrolyte on the lithium metal composite anode; Disposing a cathode active layer on the solid electrolyte; and A cathode current collector is disposed on the cathode active layer.
10. The method of claim 9, wherein the metal sulfide is disposed on the lithium metal layer as a continuous layer, the metal sulfide is in the form of particles partially embedded on the surface of the lithium metal layer, or wherein the metal sulfide is in the form of particles dispersed within the volume of the lithium metal layer.